ASUPAN ENERGI BERHUBUNGAN DENGAN KEJADIAN DIABETES MELLITUS PADA PASIEN LANSIA RAWAT JALAN RSUD Dr. SAIFUL ANWAR (ENERGY INTAKE IS RELATED TO DIABETES MELLITUS IN ELDERLY OUTPATIENTS AT RSUD Dr. SAIFUL ANWAR) - winny dhestina; Rakhmawati widya Safitri; anggun rindang cempaka; adhe hariani ciptaningsih (Jurnal Skala Kesehatan, 2020)
Result of National Basic Health 2018 showed that the prevalence of Diabetes Mellitus increased from 6,9% on 2013 to 8,5% on 2018. Factors affecting DM are energy intake and nutritional status. The objective of this study was to know the association between energy intake and other factors with incidence of Diabetes Mellitus (DM) in elderly patients RSUD Dr. Saiful Anwar Malang. Method of this study was cross-sectional. Sampling technique was non probability sampling by purposive sampling with total number of samples were 35. Result of this study showed that energy intake was significantly associated with incidence of DM (p=0,046). Fat, carbohydrates, fiber, cholesterol and saturated fatty acid (SFA) was not significantly associated with incidence of DM (p>0,05). There was no significantly difference between nutritional status (underweight and normal, with overweight and obese) with incidence of DM (p>0,05). In conclusion, energy intake was associated with incidence of DM in elderly patients RSUD Dr. Saiful Anwar Malang. Keyword: energy intake; diabetes mellitus; elderly patients